Outcomes of retroperitoneal fibrosis-related hydronephrosis and its risk factors for poor prognosis: a multi-center retrospective cohort study in Chinese patients - Liu, Hongyan; Gao, Hui; Zhao, Jin-xia; Wong, Ut-kei; Liu, Shi-bo; Liu, Jian; Zhang, Ge; Wang, Kuan-ting; Wang, Yan; Zhao, Lin; Ma, Xiang-bo; Lu, Yue-wu; et al. (Frontiers in Medicine, 2024)
Objective Retroperitoneal fibrosis (RPF) is a rare disease characterized by the presence of fibroinflammatory tissue that surrounds the abdominal aorta and the iliac arteries and often entraps the ureters. Hydronephrosis is a common complication of RPF, however, its clinical features and outcomes have not been well elucidated. Methods A total of 115 RPF-related hydronephrosis patients have been recruited from 9 clinical centers in China since March 2010. They were followed up until death or September 2021, whichever came first. Results The mean age at diagnosis was 58.83 ± 12.13 years, and 80 patients (69.57%) were men. The median disease duration was 3.00 (1.00, 9.00) months. Renal impairment was observed in 88.35% of the patients, and 49.57% showed bilateral ureteral involvement. Elevated ESR and CRP were presented in 80.28 and 62.02% of the patients, respectively. Overall, 28.21% (11/39) of the patients had increased IgG4 levels, and 41.38% (12/29) showed positive pathological IgG4 staining (IgG4+/IgG+ ≥ 40% or IgG4+ ≥ 10/HPF). Among them, three patients were diagnosed as IgG4RD. After 60.43 ± 34.53 months of follow-up, 36 patients had poor prognosis, which was associated with severe kidney impairment, bilateral hydronephrosis and inflammation status (elevated ESR and IgG) at diagnosis by case–control study. eGFR and creatinine were independent risk factors after adjusting for all other significant associations (p = 0.002 and p = 0.067, respectively). Glucocorticoid-based therapy could reduce the time of stenting, decrease the need for long-term ureteral stenting/percutaneous nephrostomy (PNS)/ureterolysis, increase the rate of mass shrinkage, and reduce the new requirement of hemodialysis compared to surgery-only strategy for RPF-related hydronephrosis patients in need of renal drainage, but did not reduce new-onset renal atrophy. Conclusion Severity of kidney dysfunction and inflammation status were related to the poor prognosis of hydronephrosis induced by RPF. More efficient interventions and strategies are needed to further improve outcomes.